Integrating Javanese Code-Mixing in Short Film Ayah for Culturally Responsive Speaking Instruction in Indonesian Classrooms - Sari, Lusi Komala; Daningtia, Alya Qurrotuaini; Onwuagboke, Bede Blaise Chukwunyere (Lucerna : Jurnal Riset Pendidikan dan Pembelajaran, 2025)
This study explores how internal code-mixing in the short film Ayah reflects Javanese cultural values in family interactions. Framed by the ethnography of communication and sociolinguistic perspectives, it aims to identify the forms and functions of Indonesian–Javanese code-mixing and its role in cultural expression. Using a qualitative descriptive method, data were drawn purposively from fifteen dialogue scenes containing internal code-mixing. Analysis employed Dell Hymes’ SPEAKING model to reveal the communicative and cultural meanings of the utterances. Validity was ensured through theoretical triangulation and inter-rater agreement, and ethical standards were met through proper attribution and representation. Findings show that internal code-mixing, particularly using Javanese krama, functions to express politeness, affection, and identity. These linguistic choices embody core cultural values such as unggah-ungguh (etiquette), respect for elders, and familial harmony. The study concludes that internal code-mixing serves not only communicative but also symbolic purposes. It highlights the potential of culturally rich films as pedagogical resources to foster learners’ sociopragmatic competence and contextual speaking skills.